Relationship between Mobile Unit Activities and Blood Availability at UDD PMI Surakarta City Trimester 2 of 2022 - Syarifah Syarifah; Titis Wahyuono; Elfrida Aryani Liwu (PT FORMOSA CENDEKIA GLOBAL, 2023)
To find out the relationship between mobile unit activities and blood availability at UDD PMI Surakarta City in the 2nd trimester of 2022. This study used a correlation test with a quantitative approach, namely linking one variable to another. Next, statistical tests (Univariate and Bivariate) use SPSS software. Data was obtained from the register book to determine the number of Mobile unit activities and blood availability at UDD PMI Surakarta City in the 2nd trimester of 2022. From the Mobile unit activities at UDD PMI Surakarta City during the 2nd trimester in 2022, 10,027 blood bags were obtained, based on the results of the Test Kendall Tau obtained a significance value of 0.00 (less than 0.01). This can mean that the relationship between Mobile Unit activity and blood availability is perfect. The relationship between Mobile Unit activities and blood availability is perfect and really helps UDD PMI in meeting blood demand.